2022
DOI: 10.1007/s10886-022-01391-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Green Gram Plant Volatile Blends in the Behavior of Arctiid Moth, Spilosoma obliqua

Abstract: Larvae of Spilosoma obliqua Walker (Lepidoptera: Arctiidae) feed on the leaves and owers of green gram [Vigna radiata (L.) Wilczek] and reduce seed yield. Therefore, it is interesting to observe whether undamaged (UD) and insect-damaged (ID, plants after feeding by S. obliqua larvae) plants cause attraction of conspeci c adult moths. Females showed attraction towards volatile blends of UD, ID and mechanically-damaged (MD) plants of three green gram cultivars [PDM 54 (PDM), Pusa Baisakhi (PUSA) and Samrat (SAM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…The results of the present study on the olfactory responses of D. indica adults revealed that virgin females and gravid females had similar behavioral response to volatiles of undamaged T. anguina plants, which indicates that the response to host plant volatiles is not associated with the physiological state (mating status) of the female. 30,35,39 Therefore, we used virgin D. indica females throughout the olfactory bioassays. However, olfactory responses of virgin and gravid females could be different when volatiles from undamaged plants were tested against volatiles from conspecific-damaged plants.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The results of the present study on the olfactory responses of D. indica adults revealed that virgin females and gravid females had similar behavioral response to volatiles of undamaged T. anguina plants, which indicates that the response to host plant volatiles is not associated with the physiological state (mating status) of the female. 30,35,39 Therefore, we used virgin D. indica females throughout the olfactory bioassays. However, olfactory responses of virgin and gravid females could be different when volatiles from undamaged plants were tested against volatiles from conspecific-damaged plants.…”
Section: Discussionmentioning
confidence: 99%
“…56 Our findings implicate that HIPVs not only aid predators to locate the herbivorous insect pest but also help conspecific adults to further attract the attacked host plant. 39,[65][66][67][68][69] A number of studies revealed that larvaeinduced plant volatiles attracted conspecific-adults such as larval feeding of the light brown apple moth [Epiphyas postvittana (Walker)] on apple seedlings attracted adult moths on the insect-damaged apple seedlings in comparison to undamaged plants, 68 and feeding by the cabbage moth [Mamestra brassicae (Linnaeus)] larvae on cabbage plants attracted more conspecific adult moths in comparison to undamaged plants. 66 Thus, feeding by D. indica larvae on T. anguina plants in crop fields could cause the conspecific females to lay more eggs on T. anguina plants, which could lead to further damage by the larvae on T. anguina plants.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations